Beyond bilingualism: an additive trilingual equity agenda for Indigenous English education in Latin America - Fabre-Triana, Paula; Faytong-Haro, Marco; Contreras-Falcones, Alexis; Angulo-Prado, Andrea; Paez-Tobar, Angelike; Fabre-Merchan, Paolo (Frontiers in Education, 2025)
English language education is expanding across Latin America, yet Indigenous populations continue to face systemic barriers in accessing quality instruction. This perspective examines the structural, cultural, and pedagogical challenges that shape Indigenous students’ experiences and develops four through lines: the inadequacy of one size fits all teaching models that ignore multilingual realities; the fraught relationship between English and cultural identity when programs are not designed additively; emerging examples such as trilingual teacher preparation, intercultural universities, and technology assisted instruction that show context sensitive promise; and the policy implications of these patterns for sustainable scale. We argue that effective English instruction does not have to undermine Indigenous identity. We propose an Additive Trilingual Equity Model that conditions English as a third language on institutional guarantees for Indigenous language literacy and academic Spanish, and we introduce practical criteria for judging whether programs are scalable and sustainable in Indigenous settings. Applying this lens to widely cited initiatives such as Plan Ceibal, English Opens Doors, and Naatik, we distinguish between access gains and transferability, and we stress the need for independent long term evaluation. The article concludes with a regionally grounded research and policy agenda and three falsifiable predictions about the conditions under which English learning can rise without eroding Indigenous languages. The analysis reframes success from adding English to securing multilingual learning conditions that endure, offering a path to protect linguistic rights while expanding access to global language skills.